(untitled) (American Journal of Islam and Society, 2010)
On 12 January 2010, the world witnessed the complete devastation of Haiti, this hemisphere’s first black independent nation. That this is evil in its nature is disputed by none (Plato uses evil to refer to poverty, disease, pain, sickness, harm, injustice, badness, discord, chaos, disorder, ugliness, weakness, deformity, and other things).1 What is deliberated, however, are the causes, effects, and what to do next. More appropriately, the international community rallied to help the innocent and helpless Haitians instead of trying to justify why this particular earthquake occurred. In this editorial, I seek to provoke philosophical debate and refocus theological attention on evil in the world, while hoping to raise more pointed questions about those who attempted to provide absolute answers for this particular earthquake. The very next day, the infamous televangelist Pat Robertson of the “700 Club” dared to offer an apparent justification and cause of this earthquake.2 Much has been stated about his insensitivity and the fabricated story he cited. But the absurdity of his argument and the underlying ideology are even more troubling. He concluded that God was punishing the Haitians because their ancestors had made a “pact with the Devil” to help them gain independence from France. Thus, God has cursed all generations of Haitians. Setting aside his lack of consideration of how this pact could have been made, the underlying conclusion is that the Haitians’ ancestors abandoned God in favor of the Devil (who had become effective in their quest for independence) and since then God has been taking revenge upon them, even on those citizens who follow other religions and thus have nothing to do with that alleged sin, either then or now. What does that say about God and His omnipotence and justice? Philosophers and theologians have long struggled with these questions ...